1699 N.H. Laws ch. 1: An Act for Restraining and Punishing Privateers and Pirates: Penalty for Nonappearance in Armes, in 1 Laws of New Hampshire: Province Period 656 (1904) - (:unkn) unknown (My University, 1699)
"And all and every person and persons that upon orders given him or them shall refuse to repair immediately with his or their Arms well fixed and Ammunition, to such place or places as shall be appointed by the said Officer, and not readily obey his Command in the premises, shall be Imprisoned without Bail or Mainprize, until the next General Session of the Peace within the same County, and by the Justices of the same Court fined, not exceeding Ten Pounds, or be corporally punished, not exceeding Ten Stripes, at the direction of the Justices."
Keywords: REQUIRED POSSESSION